The Effect of Corporate Social Responsibility, Inventory Intensity, and Capital Intensity on Tax Aggressiveness - Wulandari Cahyani Putri; Lindawati Lindawati (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study is motivated by the phenomenon of corporate efforts to minimize tax burdens through tax planning and tax aggressiveness strategies. Companies tend to reduce their tax obligations through both legal mechanisms, such as tax avoidance, and illegal practices, such as tax evasion. In this context, firms are often evaluated based on their ability to exploit gaps in tax regulations to reduce payable taxes. Therefore, this study aims to analyze the effect of Corporate Social Responsibility, Inventory Intensity, and Capital Intensity on tax aggressiveness in energy sector manufacturing companies listed on the Indonesia Stock Exchange. This research adopts a quantitative approach using secondary data derived from annual financial reports. The sample consists of eighteen companies observed over a five-year period, resulting in ninety observations selected through purposive sampling. The data are analyzed using panel data regression with the assistance of EViews software. The analysis includes descriptive statistics, classical assumption tests, and hypothesis testing through t-test and F-test. The findings indicate that Corporate Social Responsibility, Inventory Intensity, and Capital Intensity simultaneously influence tax aggressiveness. Partially, Corporate Social Responsibility has a significant effect on tax aggressiveness, while Inventory Intensity and Capital Intensity do not show significant effects. These results suggest that non-financial factors play a more prominent role in shaping corporate tax behavior.